Model construction and verification of Financial Management Based on Machine Learning Algorithm - Chen, Yuchan (Procedia computer science, 2025)
With the rapid development of big data and artificial intelligence technology, machine learning algorithms are increasingly widely used in the field of financial management. This paper first summarizes the basic principles of machine learning algorithms, and then deeply analyzes their specific applications in financial management. By comparing traditional financial management methods with those based on machine learning algorithms, this paper reveals the advantages of machine learning algorithms in improving the efficiency, accuracy and intelligence of financial management. On this basis, this paper verifies the effectiveness and reliability of the proposed financial management model based on machine learning algorithm through experiments. The model based on machine learning algorithm can more accurately predict the financial situation of enterprises, timely detect potential financial risks, and provide strong support for corporate decision-making.